Progression of diabetes is associated with changes in the ileal transcriptome and ileal‐colon morphology in the UC Davis Type 2 Diabetes Mellitus rat - Brian D. Piccolo (Wiley, 2021)
Abstract Deterioration in glucose homeostasis has been associated with intestinal dysbiosis, but it is not known how metabolic dysregulation alters the gastrointestinal environment. We investigated how the progression of diabetes alters ileal and colonic epithelial mucosal structure, microbial abundance, and transcript expression in the University of California Davis Type 2 Diabetes Mellitus (UCD‐T2DM) rat model. Male UCD‐T2DM rats (age ~170 days) were included if <1‐month (n = 6, D1M) or 3‐month (n = 6, D3M) post‐onset of diabetes. Younger nondiabetic UCD‐T2DM rats were included as a nondiabetic comparison (n = 6, ND, age ~70 days). Ileum villi height/crypt depths and colon crypt depths were assessed by histology. Microbial abundance of colon content was measured with 16S rRNA sequencing. Ileum and colon transcriptional abundances were analyzed using RNA sequencing. Ileum villi height and crypt depth were greater in D3M rats compared to ND. Colon crypt depth was greatest in D3M rats compared to both ND and D1M rats. Colon abundances of Akkermansia and Muribaculaceae were lower in D3M rats relative to D1M, while Oscillospirales, Phascolarctobacterium, and an unidentified genus of Lachnospiraceae were higher. Only two transcripts were altered by diabetes advancement within the colon; however, 2039 ileal transcripts were altered. Only colonic abundances of Sptlc3, Enpp7, Slc7a15, and Kctd14 had more than twofold changes between D1M and D3M rats. The advancement of diabetes in the UCD‐T2DM rat results in a trophic effect on the mucosal epithelia and was associated with regulation of gastrointestinal tract RNA expression, which appears more pronounced in the ileum relative to the colon.